Grid nanoindentation on calcium sulfoaluminate (CSA)-Kaolinite pastes. (13th June 2022) - Zakira, Umme; Bajpayee, Aayushi; Pharr, Matt; Banerjee, Sarbajit; Birgisson, Bjorn
Highlights: Grid Nano-indentation on kaolinite infused calcium sulfoaluminate (CSA) cement system. Nanomechanical mapping and roughness RMS ensuring data reliability. Statistical analysis coupled with microstructural investigation rendering phase identification and validation. Abstract: Calcium sulfoaluminate cement (CSA) has garnered attention in the construction industry as a low carbon footprint binder. CSA-kaolinite is a potential building material of the future and holds promise as a sustainable cement-based concrete. While the macroscopic properties of CSA cement have been extensively investigated, the nanomechanical properties of CSA-kaolinite remain largely underexplored. This study investigates the nanomechanical properties (elastic modulus and hardness) of CSA-kaolinite samples by using a grid nanoindentation approach, which enables both spatial mapping and indentation depth studies. A frequency-histogram-derived probability density function (PDF) model was found to fit well to the experimental dataset and revealed that the dominant phase of the system is ettringite irrespective of incorporation of kaolinite. The elastic modulus of ettringite was determined to be 20.8 and 17.5 GPa for samples without and with kaolinite, respectively, which is consistent with results from previous studies. Furthermore, a microstructural investigation confirmed ettringite as the major hydration phase of the system. Descriptive statistics, t-tests, and Kruskal–Wallis analysis of variance (ANOVA) were performed to determine if the measurements belong to a different group of populations. Non-parametric tests were found to be more accurate for these highly heterogeneous and skewed groups of cement-based materials. The mechanical properties from the samples of CSA with kaolinite and from those without kaolinite were found to be significantly statistically different which demonstrates that the nanoindentation test results are from two different sets of samples. The addition of kaolinite, as much as 10 wt%, in the CSA system has a trivial effect on the microscale mechanical properties which broadens the perspective of utilizing the kaolinite as a building constituent prolonging the advantages of infusing sustainability in the construction industry.